PROPOSING INNOVATION MANAGEMENT MODEL IN LARGE CORPORATION - Santoso, Aloysius Budi; Irawan, Agustinus Purna; Suhartanto, Eko (Graduate Program of Universitas Tarumanagara, 2023)
When business enters industry 4.0 era, emerging technologies are evolving and utilized to promote business performance. This signifies disruption among companies especially in large corporations due to its stiffness and slowness in response while startups or small companies are prone to response quickly. Previous studies suggest innovation to overcome this condition so that those large corporation could still enhance its performance in this industry era. Thus, several studies of them have been considered to propose an Innovation Management Model in Large Corporation. The result shows that in order to promote business performance, there are several factors needed to be considered such as: 1) Leadership, 2) Culture, 3) Support, 4) Innovation Process and 5) Business Performance. This study offers an interesting innovation management model to achieve business performance. This model consists of prementioned five components. From the proposal, business performance in large corporations is driven by innovation process. Meanwhile, in promoting this process, those large corporations need to promote leadership and culture. This model also suggests support for accelerating the process. This finding and contribution may give an opportunity for researchers to test the model for their future research.